An Effective Instructor: A Deep Look at Students and Instructors Experiences and Perspectives - Leila Jouybari (Strides in Development of Medical Education, 2010)
Background & Objective : In a clinical environment where students learn their professions practical skills and become acquainted with their future roles and responsibilities having a capable and effective clinical instructor is vital to assure an appropriate atmosphere for learning and applying skills and organizing learning in a clinical environment This study aimed to determine the characteristics of an effective instructor according to nursing & midwifery students and instructors point of view   Methods : In this qualitative phenomenological study 30 students and 8 instructors of nursing and midwifery in Gorgan University of Medical Sciences were selected using purposive sampling method Data was collected using semi structured deep and interactive interviews They were analyzed using an approach recommended by Collaizi   Results : The analysis of documents revealed three common concepts of characteristics of an effective clinical instructor according to the students and instructors point of view They included practical and scientific competencies educational management competencies and good behavior Participants also mentioned a variety of issues as inhibitors for effectiveness of an instructor and clinical learning The most important of them were lack of enough facilities old educational centers a paternalistic state created by medical doctors in educational centers and reluctance of nursing students to their career   Conclusion : Our findings suggest that a systematic and alternative thinking is essential for improvement of a clinical education setting The enhancement of the instructors theoretical and clinical skills should accompany physical structural and qualitative changes of educational centers